2005
DOI: 10.1002/anie.200501358
|View full text |Cite
|
Sign up to set email alerts
|

Capsules and Star‐Burst Polyhedra: An [Ag2L2] Capsule and a Tetrahedral [Ag4L4] Metallosupramolecular Prism with Cyclotriveratrylene‐Type Ligands

Abstract: Cyclotriveratrylene (CTV) is a macrocyclic host molecule that strongly favors a crown conformation, which gives it a bowl shape with a shallow molecular cavity.[1] Indeed, despite CTV being known for over 40 years, the alternative saddle conformation has only recently been isolated by the rapid quenching of a hot solution or melt, [2] or within a novel CTVbased cryptophane.[3] The bowl-shaped CTV is a cyclic trimer which has a distinctly spiked, pyramidal aspect. We wish to exploit this characteristic to creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 58 publications
2
51
0
Order By: Relevance
“…When considering some of the largest supramolecular container assemblies formed to date [16,19,23,[47][48][49][50][68][69][70][84][85][86], hydrogen-bonded pyrogallol- [4]arene capsules (either dimeric or hexameric) are useful for the encapsulation of reasonably large non-solvent molecules, as identified by X-ray diffraction studies [96][97][98][99][100][101][102][103]116,[118][119][120]. From the work reviewed in this article, we have also shown that they are also useful templates for metal-organic analogues [116,[118][119][120][121]124,127].…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 97%
See 2 more Smart Citations
“…When considering some of the largest supramolecular container assemblies formed to date [16,19,23,[47][48][49][50][68][69][70][84][85][86], hydrogen-bonded pyrogallol- [4]arene capsules (either dimeric or hexameric) are useful for the encapsulation of reasonably large non-solvent molecules, as identified by X-ray diffraction studies [96][97][98][99][100][101][102][103]116,[118][119][120]. From the work reviewed in this article, we have also shown that they are also useful templates for metal-organic analogues [116,[118][119][120][121]124,127].…”
Section: Concluding Remarks and Future Prospectsmentioning
confidence: 97%
“…10B) or tetrameric (Fig. 10C) capsular architectures with the 3-pyridyl or 4-pyridyl derivatives, respectively [84]. The tetrameric capsule has a host at each vertex of a tetrahedron, and the pyridyl moieties are bound to silver centres that in some cases also have bound acetonitrile molecules on the exterior of the capsule, resulting in a star-burst tetrahedron.…”
Section: Metal-organic/ionic Capsules and Capsule-like Architecturesmentioning
confidence: 98%
See 1 more Smart Citation
“…Tripodal derivatives such as those shown in Scheme 1 are chiral. The self-assembly of derivatised CTVs with metal cations is well established, and coordination polymers, [35][36][37] discrete metallocages, [38][39][40][41][42] and mechanically interlocked architectures [43][44][45] are known. However, the chemistry of mixed ligand systems is generally limited to the solution-phase, and we have recently demonstrated how the formation and manipulation of homo-and heteroleptic [Pd 6 L 8 ] 12+ octahedral cages can be controlled with high fidelity.…”
Section: -13mentioning
confidence: 99%
“…The self-assembly of derivatised CTVs with metal cations is well established, and coordination polymers, [35][36][37] discrete metallo-cages, [38][39][40][41][42] and mechanically interlocked architectures [43][44][45] are known. However, the chemistry of mixed ligand systems is generally limited to the solution-phase, and we have recently demonstrated how the formation and manipulation of homo-and heteroleptic [Pd 6 L 8 ] 12+ octahedral cages can be controlled with high fidelity.…”
Section: Introductionmentioning
confidence: 99%